Factors affecting successful endoscopic sclerotherapy for oesophageal varices. - Rose, J D (1983)
Forty patients with bleeding oesophageal varices were studied during treatment by endoscopic sclerotherapy to discover what factors determine successful outcome. Large varices required more injections than small varices for obliteration, and rebleeding during treatment occurred only in patients with large varices. Radiological studies with sclerosant contrast mixture showed that in two groups of varices of comparable size, intravenous sclerosant was significantly more effective, leading to thrombosis in 8/10 as opposed to only 3/10 after paravasal injection (p less than 0.05). Intravenous contrast was rapidly cleared upwards, whereas paravasal contrast formed a rounded opacity alongside the vein that persisted for approximately 90 minutes, responsible for the complications of oesophageal ulceration and stenosis.